Peddling Wonderment, Selling Privilege: Launching the Market for Medieval Books in Antebellum New York - Scott Gwara (Perspectives Médiévales)
Medieval and Renaissance manuscripts were collected in North America from about 1820. Four key sources of them can be identified: 1. Ancestral ownership of books brought by early settlers; 2. Acquisitions by missionaries and scholars; 3. Mementos acquired by elites on European Grand Tours; 4. Purchases by bibliophiles from international sales catalogues, domestic booksellers, and auctions of imported volumes. Examples of such manuscripts are identified in this article, and their early owners are recognized as pioneering collectors. A small but profitable commerce in manuscripts emerged in major cities, chiefly New York, where the firm of Daniel Appleton held an early monopoly. Appleton’s had acquired two chests of illuminated manuscripts in Paris. Selling was a challenge, however. Since medieval and Renaissance manuscripts in the New World were unreadable books because of language and script, enterprising booksellers were forced to develop innovative ways to sell them. Appleton’s, for example, used “placement advertising” to sell its manuscripts, publishing articles on medieval topics that mentioned or evoked manuscripts. Two ways of marketing manuscripts came to predominate by the middle of the nineteenth century. The book dealer Joseph Sabin promoted “artifactual reading.” He emphasized the materiality of manuscripts, their possession by fanatic monks, their esoteric rarity, and the possibility of owning the lifetime work of a sensitive, if unschooled, artist. Sabin detailed his ideas in the auction catalogues he authored. George P. Philes, by contrast, published a newsletter called Philobiblion, in which he debunked Sabin’s manuscript mythologies. His marketing was bibliographical. Manuscripts, Philes suggested, were not rare, nor the life-works of religious, nor objects of mystical veneration. He marketed elite collectors who considered themselves New World aristocrats. Philes got his novel ideas from Archives du Bibliophile, a Paris journal published by Anatole Claudin. Philes translated many of its articles and even sold manuscripts that had been offered in Archives. This effort was a rare instance of influence by the Paris booktrade on the New York market.